Phosphorylation of myofibrillogenesis regulator‐1 activates the MAPK signaling pathway and induces proliferation and migration in human breast cancer MCF7 cells. Issue 17 (24th July 2014) - Gong, Yuyan; He, Hongwei; Liu, Hong; Zhang, Caixia; Zhao, Wuli; Shao, Rong-guang
Abstract : Myofibrillogenesis regulator‐1 (MR‐1) has been characterized as a tumor promoter in many cancers. However, its mechanism of action has not been fully elucidated. Here, we report that MR‐1 is overexpressed in human breast cancer cells and participates in tumor promotion in human breast cancer MCF7 cells by activating the ERK1/2 signaling pathway. MR‐1 interacts with MEK1/2 and ERK1, and its N‐terminal sequence plays a major role in promoting the MEK/ERK cascade. Furthermore, six phosphorylation sites of MR‐1 were identified, and phosphorylation at S46 was shown to be critical for the activation of MEK/ERK. Therefore, our findings suggest that MR‐1 functions as a tumor promoter in MCF7 cells by activating the MEK/ERK signaling. Abstract : MR‐1 is overexpressed in breast cancer cells and tissues. MR‐1 plays a tumor‐promoting role in MCF7 cells by activating the MEK/ERK cascade. MR‐1 interacts with MEK1/2 and ERK1. Six phosphorylation sites of MR‐1 were identified by LC–MS/MS. Phosphorylation of MR‐1 at S46 is crucial for its function in activating the MEK/ERK cascade.